PENGARUH PEMBERIAN EKSTRAK UBI JALAR UNGU DAN EKSTRAK BUAH BIT TERHADAP KADAR KOLESTEROL PADA TIKUS WISTAR YANG DIBERI DIET TINGGI LEMAK - Tohjiwa, G. Raditya; Wahyuniari, Ida Ayu Ika; Linawati, Ni Made; Arijana, I G Kamasan Nyoman (E-Jurnal Medika Udayana; Vol 11 No 6 (2022): E-Jurnal Medika UdayanaDO - 10.24843/MU.2022.V11.i06.P02, 2022)
Cardiovascular disease is a disease that often occurs in Indonesia. Cholesterol and free radicals can stimulate an increase in oxidative stress on the walls of the coronary arteries which can trigger coronary heart disease. Ipomea Batatas and Beta Vulgaris L contain flavonoids and betalains which is useful to lower cholesterol levels in the body to prevent cardiovascular disease. This study aimed to determine the effect of the combination of purple sweet potato and beetroot extract on cholesterol levels in rats fed a high-fat diet. The study design was an experimental study using the Post Test Only Control Group Design method with a sample of 24 male wistar rats fed a high-fat diet and divided into 4 groups. Aquadest was given to the control group (K-) while Ipomea Batatas extract (P1), Beta Vulgaris L extract (P2) and a combination of Ipomea Batatas and Beta Vulgaris L extract (P3) were given to the treatment group. Cholesterol levels will be tested using photometrics with Diasys Cholesterol reagent using blood serum. Data is analyzed with One Way ANOVA. This research showed that there were significant differences in cholesterol levels between the control group and the treatment group given purple sweet potato extract and combination extract with a P value <0.05. The cholesterol level of Group K- 116.8 mg/dL, P1 88.8 mg/dL, P2 99.0 mg/dL, and P3 92.5 mg/dL In conclusion, purple sweet potato extract and the combination extract could reduce cholesterol levels in male wistar rats fed a high-fat diet. Keywords: Ipomoea batatas, Beta vulgaris L, Cholesterol Levels